2015
DOI: 10.1188/15.cjon.19-05ap
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Nonpharmacologic Interventions for Treatment-Related Symptoms in Women With Ovarian Cancer

Abstract: Nonpharmacologic interventions for treatment-related symptoms were complex, with an average of 4.4 components. Intervention delivery, setting, and exposure varied widely across studies. Only three studies contained details sufficient to replicate the intervention. Lack of clarity in intervention reporting may explain perceptions of clinically inefficacious symptom management in this context. Greater attention to reporting would facilitate better translation of interventions into practice and when addressing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Women with ovarian cancer demonstrated continued symptoms of depression and anxiety for cancer survivors who had undergone chemotherapy treatment, according to a meta-analysis of prevalence rates ( 4 ). Ineffective or prolonged management of treatment could contribute to worsening of symptoms, treatment noncompliance and even reduced health-related quality of life ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Women with ovarian cancer demonstrated continued symptoms of depression and anxiety for cancer survivors who had undergone chemotherapy treatment, according to a meta-analysis of prevalence rates ( 4 ). Ineffective or prolonged management of treatment could contribute to worsening of symptoms, treatment noncompliance and even reduced health-related quality of life ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non‐pharmacological interventions such as nurse‐led telephone interventions, pain‐reducing or psycho‐educational programmes to address reductions in HRQoL have shown no convincing effect in women with ovarian cancer (Cook et al, 2015; Davis & Carpenter, 2015; Kalter et al, 2018). Likewise and despite the increased attention given to exercise oncology (McTiernan et al, 2019), only a few small‐scaled intervention studies ( n = 17–30), are available examining HRQoL in women with ovarian cancer undergoing chemotherapy, which is why the results must be applied with caution (Mizrahi et al, 2015; Moonsammy et al, 2013; Newton et al, 2011; von Gruenigen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using a meta-analysis of prevalence rates, it was identified that females with ovarian cancer who had undergone chemotherapy treatment demonstrated continued symptoms of depression and anxiety (4). Ineffective or prolonged management of treatments may contribute to the worsening of symptoms, treatment noncompliance and even a decrease in health-associated quality of life (5). Although previous studies have proposed certain improvements in early diagnosis and anticancer therapies for ovarian carcinoma (6)(7)(8)(9), metastasis remains the major challenge in the treatment of ovarian carcinoma.…”
Section: Introductionmentioning
confidence: 99%